Innovation in Social Care - Lefevre, Michelle; Huegler, Nathalie; Lloyd, Jenny; Owens, Rachael; Damman, Jeri; Ruch, Gillian; Firmin, Carlene (Policy Press, 2024)
Available Open Access under CC-BY-NC-BD licence. Based on the findings of the Innovate Project, a four year pan-UK study to identify the processes of innovation in care, this book asks: how can services be re-envisioned and transformed through innovation? The authors provide an overview of the project findings and offer insights into the core conditions necessary for socially just and practice-congruent social care innovation that responds to the distinctive, contemporary safeguarding concerns facing young people.. Essential reading for anyone engaged in social care practice and innovation, as well as those undertaking continuing professional development, this book will aid the reader in developing a conceptual understanding of their experiences and support them in designing more informed responses to the challenges they face.